Formulation And Evaluation Of Controlled Porosity Osmotic Pump Of Valsartan - Kapoor, Devesh (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTControlled porosity osmotic pump contains water soluble additive in the coating membrane which in contact with aqueous environment dissolves and outcome in creation of micro porous membrane. The resulting membrane is substantially permeable to both water and dissolved drug. The goal of this investigation is, to gain the benefit of pH and confrontation independent release performance leading to similar in vitro / in vivo delivery. Osmotically driven system embrace a prominent place because of their trustworthiness and knack to deliver the contents at predetermined zero-order rates for extended periods. In the present investigation, efforts have been made to study the release mechanism of drug having low water solubility by means of controlled porosity osmotic pump. The capsule membrane was prepared by phase inversion technique. The delivery orifices so formed were inveterate by release of an encapsulated dye from the capsule and scanning electron microscope (SEM).The drug selected for this study, valsartan, has low water solubility and hence is unable to create osmotic pressure to cause drug release. To augment the solubility and its osmotic pressure, this study was conducted with a solubility enhancer HPMC (Hydroxy propyl methyl cellulose), PEG-6000 and osmogents KCl. Valsartan has a short plasma half life of 3-5 h. Hence, valsartan was chosen as a model drug with an aspire to develop a controlled porosity system for periods of 9 hours. This system was found to deliver valsartan at a zero order rate for 9 hours.